A graphene oxide-based composite aerogel adsorbent and its preparation method and application
By introducing polyethyleneimine, acrylamide and methacryloyloxyethyltrimethylammonium chloride into graphene oxide adsorbents, the composite aerogel adsorbents are formed, which solves the problem that the dispersion of existing graphene oxide adsorbents in water is not conducive to recovery and limited adsorption performance, and achieves the effect of stable structure, easy recovery and high-efficiency adsorption.
Patent Information
- Application Number
- CN202211427783.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-11-15
AI Technical Summary
The dispersion of existing graphene oxide adsorbents in water is not conducive to recovery, and their adsorption properties are limited, making it difficult to apply in industrial production.
By combining polyethyleneimine and acrylamide with graphene oxide, a large number of oxygen-containing functional groups and amino functional groups are introduced, and polymerized with methacryloyloxyethyltrimethylammonium chloride to form a composite aerogel adsorbent. This method not only improves the binding stability of the adsorbent, but also increases the pore structure and active adsorption sites.
It has achieved stable structural structure, easy recovery, excellent adsorption performance and good regeneration performance of graphene oxide composite aerogel adsorbent, and is suitable for industrial production.
Smart Images

Figure CN115888663B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite aerogel adsorbent, in particular to a graphene oxide-based composite aerogel adsorbent and a preparation method and application thereof, belonging to the technical field of adsorbents. Background Art
[0002] The surface of graphene oxide (GO) contains a large number of oxygen-containing functional groups, such as hydroxyl, carboxyl and epoxy groups. It has the advantages of good hydrophilicity and large specific surface area, and has received extensive attention in the field of adsorbents. However, the ability of pure GO to adsorb pollutants is limited. In order to enhance its adsorption capacity, GO needs to be modified, or other substances with good adsorption properties need to be introduced into GO to prepare GO-based composite materials. Relevant literature reports that GO is modified by amino functionalization and amino groups are introduced into the GO surface to adsorb anionic pollutants. This method improves the adsorption performance of GO, but the prepared adsorbent is obviously not conducive to recycling when dispersed in water.
[0003] In order to facilitate the recovery of adsorbents, relevant literature reports the introduction of magnetic substances to the surface of GO, and the use of an external magnetic field to separate the adsorbent saturated with adsorption from the solution. However, since the introduced magnetic substances themselves do not have good adsorption properties, the adsorption properties of GO cannot be greatly improved, and the preparation process conditions are relatively high, which is not conducive to industrial production. In order to facilitate the recovery of adsorbents and improve the adsorption performance of GO, relevant literature reports the preparation of GO-based aerogels. The aerogels always maintain their intact form during the adsorption process and have greatly improved adsorption capacity. However, the surface adsorbed active substances and aerogel structures are easily destroyed during the desorption process, resulting in a large room for improvement in regeneration performance. Therefore, it is particularly important to invent a graphene oxide-based composite aerogel adsorbent with a relatively simple preparation process, stable structure, easy recovery, excellent adsorption performance and good regeneration performance. Summary of the invention
[0004] In view of the problems existing in the prior art, the first object of the present invention is to provide a graphene oxide-based composite aerogel adsorbent, which, based on the synergistic effect between the various components, can not only carry out in situ polymerization reaction on the graphene surface, greatly improving the binding stability between the modified substance and the graphene, but also can greatly increase the pore structure and active adsorption sites of the composite aerogel.
[0005] The second object of the present invention is to provide a method for preparing a graphene oxide-based composite aerogel adsorbent, in which polyethyleneimine and acrylamide are simultaneously compounded with graphene oxide, and a large number of oxygen-containing functional groups and amino functional groups are introduced on the surface of the adsorbent. In addition, acrylamide can also undergo a polymerization reaction with methacryloyloxyethyltrimethylammonium chloride, thereby enhancing the electronegativity of the adsorbent surface and improving the adsorption capacity of the catalyst for anionic pollutants.
[0006] The third object of the present invention is to provide an application of a composite aerogel adsorbent for adsorbing organic pollutants in sewage. The adsorbent provided by the present invention presents an overlapping layer and a porous structure, with a large number of folds and holes, which, on the one hand, increases the contact area between the adsorbent and the organic matter in the sewage, and on the other hand, provides more active adsorption sites, which is conducive to the adsorption process.
[0007] In order to achieve the above technical purpose, the present invention provides a method for preparing a graphene oxide-based composite aerogel adsorbent, comprising the steps of adding acrylamide to a graphene oxide suspension and mixing uniformly to obtain a mixed suspension; adding ammonium persulfate and N,N-methyleneacrylamide to methacryloyloxyethyltrimethylammonium chloride and mixing thoroughly to obtain a prepolymer; adding a polyethyleneimine aqueous solution to the prepolymer to obtain a prereaction liquid; adding the prereaction liquid to the mixed suspension, and sequentially adding an ammonium persulfate aqueous solution and an N,N-methyleneacrylamide aqueous solution thereto, and sequentially subjecting the mixture to stirring, gelling reaction, washing and freeze-drying to obtain the mixed suspension.
[0008] The preparation method provided by the present invention adopts a three-step method to prepare a mixed suspension and a pre-reaction liquid respectively, and then mix the two to react. On the one hand, it can enhance the binding force between the polymer and the graphene oxide matrix to prevent the matrix from falling off during adsorption and desorption; on the other hand, it can enrich the pore structure and active sites of the organic polymer and improve the adsorption performance of the adsorbent.
[0009] As a preferred solution, the concentration of the graphene oxide suspension is 1 to 20 mg / mL. More preferably, the concentration of the graphene oxide suspension is 1 to 10 mg / mL. The concentration in the graphene oxide suspension must be strictly implemented in accordance with the above requirements. If the concentration of the graphene oxide suspension is too low, the volume of the solution for the final gelation reaction will be too large, which is not conducive to the gelation reaction; if the concentration of the graphene oxide suspension is too high, the probability of graphene oxide agglomeration will increase, which is not conducive to dispersion.
[0010] As a preferred solution, the mass ratio of graphene oxide to acrylamide in the mixed suspension is 1:5 to 50. Further preferably, the mass ratio of graphene oxide to acrylamide in the mixed suspension is 1:8 to 35. Too low acrylamide proportion is not conducive to the adsorption performance of the composite aerogel adsorbent, while too high acrylamide proportion makes the composite aerogel adsorbent easy to break during the dye adsorption process, which is not conducive to the recovery and utilization of the adsorbent.
[0011] As a preferred solution, the mass ratio of the methacryloyloxyethyltrimethylammonium chloride to ammonium persulfate is 20 to 400: 1. More preferably, the mass ratio of the methacryloyloxyethyltrimethylammonium chloride to ammonium persulfate is 40 to 250: 1. Too low a proportion of ammonium persulfate is not conducive to the initiation of the prepolymerization reaction of methacryloyloxyethyltrimethylammonium chloride, and too high a proportion of ammonium persulfate will cause the methacryloyloxyethyltrimethylammonium chloride to self-polymerize into a gel.
[0012] As a preferred solution, the mass ratio of the methacryloyloxyethyl trimethyl ammonium chloride to N,N-methylene acrylamide is 10 to 400: 1. Further preferably, the mass ratio of the methacryloyloxyethyl trimethyl ammonium chloride to N,N-methylene acrylamide is 20 to 250: 1. If the proportion of N,N-methylene acrylamide is too low, it will be unfavorable for the cross-linking process in the prepolymerization reaction of methacryloyloxyethyl trimethyl ammonium chloride, and if the proportion of N,N-methylene acrylamide is too high, methacryloyloxyethyl trimethyl ammonium chloride will self-polymerize into gel.
[0013] As a preferred solution, the mass ratio of the methacryloyloxyethyltrimethylammonium chloride to the graphene oxide is 10 to 100:1. Further preferably, the mass ratio of the methacryloyloxyethyltrimethylammonium chloride to the graphene oxide is 16 to 70:1. If the proportion of methacryloyloxyethyltrimethylammonium chloride is too low, it will not be conducive to its copolymerization with acrylamide and reduce the adsorption performance of the composite aerogel adsorbent. If the proportion of methacryloyloxyethyltrimethylammonium chloride is too high, it will gel when mixed with polyethyleneimine by ultrasound and cannot be successfully dispersed in the mixed suspension of graphene oxide afterwards.
[0014] As a preferred solution, the volume ratio of the polyethyleneimine aqueous solution to the prepolymer solution is 0.5 to 3: 1. More preferably, the volume ratio of the polyethyleneimine aqueous solution to the prepolymer solution is 0.75 to 2: 1. Too small a volume of the polyethyleneimine aqueous solution is not conducive to the complete dispersion of the polyethyleneimine, while too large a volume of the polyethyleneimine aqueous solution is not conducive to the subsequent gelling reaction.
[0015] As a preferred solution, the mass ratio of polyethyleneimine to graphene oxide is 5 to 100: 1. More preferably, the mass ratio of polyethyleneimine to graphene oxide is 10: 1 to 75: 1. Too low a proportion of polyethyleneimine is not conducive to the adsorption performance of the composite aerogel adsorbent, and too high a proportion of polyethyleneimine will cause it to gel when mixed with methacryloyloxyethyltrimethylammonium chloride by ultrasound and cannot be successfully dispersed in the mixed suspension of graphene oxide afterwards.
[0016] As a preferred solution, the mass ratio of ammonium persulfate added to the pre-reaction liquid to methacryloyloxyethyl trimethyl ammonium chloride is 1:500 to 1:10. Further preferably, the mass ratio of ammonium persulfate added to the pre-reaction liquid to methacryloyloxyethyl trimethyl ammonium chloride is 1:250 to 20. Too low a proportion of ammonium persulfate is not conducive to the gelation reaction, and too high a proportion of ammonium persulfate will waste chemical reagents on the one hand, and on the other hand, it will reduce the proportion of active substances in the composite aerogel adsorbent because too much ammonium persulfate will be mixed therein.
[0017] As a preferred solution, the mass ratio of N,N-methylene acrylamide to methacryloyloxyethyl trimethyl ammonium chloride added to the pre-reaction liquid is 1:500 to 1:5. Further preferably, the mass ratio of N,N-methylene acrylamide to methacryloyloxyethyl trimethyl ammonium chloride added to the pre-reaction liquid is 1:250 to 1:10. If the proportion of N,N-methylene acrylamide is too low, it will be unfavorable for the gelation reaction. If the proportion of N,N-methylene acrylamide is too high, on the one hand, chemical reagents will be wasted, and on the other hand, the proportion of active substances in the composite aerogel adsorbent will be reduced because too much N,N-methylene acrylamide will be mixed therein.
[0018] As a preferred solution, the conditions of the gelling reaction are: temperature of 80-120°C, time of 8-24h. More preferably, the conditions of the gelling reaction are: temperature of 80-100°C, time of 12-16h. The gelling reaction time must be strictly carried out according to the above settings. If the gelling reaction time is too long, the gel will crack and the structure will be destroyed; if the gelling reaction time is too short, the gelling will be insufficient, reducing the utilization rate of raw materials.
[0019] Furthermore, the present invention also provides a detailed preparation method of a graphene oxide-based composite aerogel adsorbent, comprising adding acrylamide to a graphene oxide suspension and ultrasonically mixing for 1 to 2 hours to obtain a graphene oxide / acrylamide mixed suspension; taking methacryloyloxyethyltrimethylammonium chloride, adding ammonium persulfate and N,N-methyleneacrylamide thereto and ultrasonically mixing for 15 to 20 minutes to obtain a methacryloyloxyethyltrimethylammonium chloride prepolymer; adding a polyethyleneimine aqueous solution to the prepolymer and ultrasonically mixing for 5 to 10 minutes to obtain a prereaction solution; adding the obtained prereaction solution to the graphene oxide / acrylamide mixed suspension, and sequentially adding an ammonium persulfate aqueous solution and an N,N-methyleneacrylamide aqueous solution thereto, and magnetically stirring for 20 to 30 minutes to obtain a precursor solution; subjecting the obtained precursor solution to a gelling reaction at 80 to 100° C., and repeatedly washing the obtained product with deionized water, and then freeze-drying the product to obtain a graphene oxide-based composite aerogel adsorbent.
[0020] The present invention also provides a graphene oxide-based composite aerogel obtained by any one of the preparation methods described above.
[0021] The present invention also provides an application of graphene oxide-based composite aerogel for adsorbing organic pollutants in sewage.
[0022] The present invention uses graphene oxide as a substrate, and for the first time, polyethyleneimine and acrylamide, which have a large number of amino groups in their molecular structures, are simultaneously compounded with graphene oxide, so that the surface of the adsorbent has a large number of oxygen-containing functional groups such as hydroxyl groups and carboxyl groups, as well as a large number of amino groups. The introduced methacryloyloxyethyltrimethylammonium chloride can be copolymerized with acrylamide as a cationic monomer, thereby enhancing the electronegativity of the adsorbent surface to a greater extent. Therefore, the graphene oxide-based aerogel adsorbent prepared by the present invention can effectively adsorb anionic pollutants in wastewater through electrostatic effects, hydrogen bonding effects, and π-π conjugation effects. The excellent aerogel structure allows the adsorbent to maintain a complete morphological structure during the adsorption process, making it easy to recycle, and a large number of adsorption active sites allow the adsorbent to have good regeneration performance.
[0023] Compared with the prior art, the beneficial technical effects brought by the present invention are:
[0024] 1) The graphene oxide-based composite aerogel adsorbent provided by the present invention can not only carry out in-situ polymerization reaction on the graphene surface based on the synergistic effect between the components, greatly improving the binding stability between the modified substance and the graphene, but also greatly increase the pore structure and active adsorption sites of the composite aerogel.
[0025] 2) In the technical solution provided by the present invention, graphene oxide is used as the adsorbent substrate. On the one hand, its surface has a large number of oxygen-containing functional groups, which is conducive to the adsorption process; on the other hand, its sheet structure is less damaged and has high stability. Furthermore, polyethyleneimine and acrylamide compounded with graphene oxide can provide a large number of amino groups for the adsorbent, and the introduced methacryloyloxyethyltrimethylammonium chloride as a cationic monomer can be copolymerized with acrylamide to enhance the electronegativity of the adsorbent surface, which is conducive to the adsorption of anionic pollutants.
[0026] 3) In the technical solution provided by the present invention, the adsorbent is prepared into an aerogel form. Its unique porous structure can increase the adsorption active sites of the adsorbent on the one hand, and on the other hand, ensure the integrity of the morphological structure of the adsorbent during the adsorption process, which is conducive to recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a high-magnification scanning electron microscope image of the graphene oxide-based composite aerogel adsorbent prepared in Example 1 of the present invention;
[0028] Figure 2 This is a high-magnification scanning electron microscope image of the graphene oxide-based composite aerogel prepared in Comparative Example 1 of the present invention;
[0029] Figure 3 This is a high-magnification scanning electron microscope image of the graphene oxide-based composite aerogel prepared in Comparative Example 2 of the present invention;
[0030] Figure 4 It is the adsorption kinetic curve diagram of Examples 1-2 and Comparative Examples 1-2 on methyl orange. DETAILED DESCRIPTION
[0031] The following examples are intended to further illustrate the present invention, rather than to limit the scope of protection of the claims of the present invention.
[0032] The graphene oxide used in the following examples and comparative examples is prepared by an improved Hummers method. The improved Hummers method for preparing graphene oxide is a conventional mature method. The graphene oxide prepared according to the existing improved Hummers method meets the technical solution of the present invention.
[0033] The specific process of preparing graphene oxide by the improved Hummers method in the present invention is: add 1g potassium persulfate and 1g phosphorus pentoxide to 20mL concentrated sulfuric acid with a mass concentration of 98%, stir and heat to 80°C, wait for potassium persulfate and phosphorus pentoxide to be fully dissolved, add 2g graphite, and continue to heat under this condition for 4.5h. After cooling, filter, wash with distilled water until neutral, and dry naturally in the air to obtain pre-oxidized graphite. Add the pre-oxidized graphite to 75mL concentrated sulfuric acid, slowly add 10.0031g potassium permanganate under ice bath, and control the temperature of this process not to exceed 20°C. After the addition is completed, heat to 35°C, react for 2h, transfer to ice bath, slowly add 160mL distilled water, control the temperature below 50°C during the water addition process, add 500mL distilled water after 2h of reaction, add 8.3mL of 30% hydrogen peroxide solution dropwise, continue stirring for 30min, and then stand for 8h. Discard the supernatant, add 800mL of 10% hydrochloric acid solution, stir for 3h and let stand for 8h. Discard the supernatant again, add 400mL of distilled water and stir for 3h. Centrifuge the resulting mixture at 5000rpm for 1h, discard the supernatant, add distilled water to the remaining part and centrifuge for 1h, wash several times until the pH is neutral, add water to adjust the concentration of the graphene oxide suspension to 6mg / mL, and store for later use. The graphene oxide in the following examples is prepared by this method.
[0034] Example 1
[0035] Take 10mL of 6mg / mL graphene oxide suspension (total amount of GO is 60mg) in a 250mL round-bottom flask, add 2mL of deionized water, and ultrasonically disperse for 1h. After the ultrasonication is completed, add 1g of acrylamide (AM) to the flask, and continue ultrasonic mixing for 1h to obtain a graphene oxide / acrylamide mixed suspension. Take another 2g of methacryloyloxyethyltrimethylammonium chloride (DMC) in a 10mL sample bottle, add 0.5mL of 20mg / mL ammonium persulfate (APS) solution (APS amount is 10mg) and 0.5mL of 20mg / mLN,N-methylene acrylamide (MBA) solution (MBA amount is 10mg), and ultrasonically mix for 15min to obtain DMC prepolymer solution. Take 2g of polyethyleneimine (PEI) in a 10mL sample bottle, add 3mL of deionized water to dissolve it, and then add it to the DMC prepolymer solution and mix it for 5min to obtain a pre-reaction solution. The pre-reaction solution was slowly added to the round-bottom flask containing the graphene oxide / acrylamide mixed suspension, and magnetically stirred for 10 minutes. Then, 1 mL of 40 mg / mL APS solution (APS amount was 40 mg) and 2 mL of 20 mg / mL MBA solution (MBA amount was 40 mg) were added, and magnetically stirred for 20 minutes to obtain a precursor solution. The precursor solution was poured into a watch glass and placed in an oven at 80°C for 16 hours of gelation reaction. After the gelation reaction was completed, the hydrogel was repeatedly soaked and washed with deionized water until the washed water was clear and transparent, and the hydrogel was freeze-dried to obtain a graphene oxide-based composite aerogel. The sample was labeled CPAM / PEI / GO(1).
[0036] Example 2
[0037] Take 10mL of 6mg / mL graphene oxide suspension (total amount of GO is 60mg) in a 250mL round-bottom flask, add 2mL of deionized water, and ultrasonically disperse for 1h. After the ultrasonic is completed, add 1gAM to the flask and continue ultrasonic mixing for 1h to obtain a graphene oxide / acrylamide mixed suspension. Take another 2gDMC in a 10mL sample bottle, add 0.5mL of 20mg / mL APS solution (APS amount is 10mg) and 0.5mL of 20mg / mL MBA solution (MBA amount is 10mg), ultrasonically mix for 15min, and obtain DMC prepolymer solution. Take 1gPEI in a 10mL sample bottle, add 3mL of deionized water to dissolve it, and then add it to the DMC prepolymer solution and mix it for 5min of ultrasonic mixing to obtain a pre-reaction solution. The pre-reaction solution was slowly added to the round-bottom flask containing the graphene oxide / acrylamide mixed suspension, and magnetically stirred for 10 minutes. Then, 1 mL of 40 mg / mL APS solution (APS amount was 40 mg) and 2 mL of 20 mg / mL MBA solution (MBA amount was 40 mg) were added, and magnetically stirred for 20 minutes to obtain a precursor solution. The precursor solution was poured into a watch glass and placed in an oven at 80°C for 16 hours of gelation reaction. After the gelation reaction was completed, the hydrogel was repeatedly soaked and washed with deionized water until the washed water was clear and transparent, and the hydrogel was freeze-dried to obtain a graphene oxide-based composite aerogel. The sample was labeled CPAM / PEI / GO(2).
[0038] Comparative Example 1
[0039] Take 10mL of 6mg / mL graphene oxide suspension (total amount of GO is 60mg) in a 250mL round-bottom flask, add 4mL of deionized water, and ultrasonically disperse for 1h. After the ultrasonic is completed, add 1gAM to the flask and continue ultrasonic mixing for 1h to obtain a graphene oxide / acrylamide mixed suspension. Take another 2g of DMC in a 10mL sample bottle, add 0.5mL of 20mg / mL APS solution (APS amount is 10mg) and 0.5mL of 20mg / mL MBA solution (MBA amount is 10mg), and ultrasonically mix for 15min to obtain a DMC prepolymer solution. Slowly add the DMC prepolymer solution to the round-bottom flask containing the graphene oxide / acrylamide mixed suspension, stir magnetically for 10min, then add 1mL of 40mg / mL APS solution (APS amount is 40mg) and 2mL of 20mg / mL MBA solution (MBA amount is 40mg), stir magnetically for 20min, and obtain a precursor solution. The precursor solution was poured into a watch glass and placed in an oven at 80°C for 16 hours for gelation reaction. After the gelation reaction was completed, the hydrogel was repeatedly soaked and washed with deionized water until the washed water was clear and transparent, and the hydrogel was freeze-dried to obtain a graphene oxide-based composite aerogel. The sample was labeled CPAM / GO.
[0040] Comparative Example 2
[0041] Take 10mL of 6mg / mL graphene oxide suspension (total amount of GO is 60mg) in a 250mL round-bottom flask, add 4mL of deionized water, and ultrasonically disperse for 1h. After the ultrasonication is completed, add 1g AM to the flask and continue ultrasonic mixing for 1h to obtain a graphene oxide / acrylamide mixed suspension. Take 1g PEI in a 10mL sample bottle, add 3mL of deionized water to dissolve it, then slowly add it to the round-bottom flask containing the graphene oxide / acrylamide mixed suspension, stir magnetically for 10min, then add 1mL40mg / mL APS solution (APS amount is 40mg) and 2mL 20mg / mL MBA solution (MBA amount is 40mg), stir magnetically for 20min, and obtain a precursor solution. Pour the precursor solution into a watch glass and put it into an oven at 80℃ for 16h of gelation reaction. After the gelling reaction is completed, the hydrogel is repeatedly soaked and washed with deionized water until the washed water is clear and transparent, and the hydrogel is freeze-dried to obtain a graphene oxide-based composite aerogel. The sample is labeled as PEI / GO.
[0042] From the high magnification scanning electron microscope image ( Figure 1 to Figure 3 ) It can be seen that the graphene oxide-based composite aerogel adsorbent prepared by the present invention ( Figure 1 ) presents overlapping layers and a porous structure. Because the gel has a large number of hydrophilic groups, it is easy to absorb water and swell. The water molecules contained in the hydrogel can form ice crystals and induce pore structures during the freeze-drying process. The abundant wrinkles and holes can provide more active adsorption sites, which is conducive to the adsorption process. The graphene oxide-based composite aerogel adsorbent without polyethyleneimine prepared in Example 1 ( Figure 2 ) has significantly fewer wrinkles. Comparative Example 2 prepared graphene oxide-based composite aerogel adsorbent without polyacrylamide ( Figure 3 ) lacks a pore structure and presents an overall multi-layer stacked structure.
[0043] For Examples 1 and 2, Comparative Examples 1 and 2, the adsorption performance was tested respectively: 2.0 mg of graphene oxide-based aerogel adsorbent was added to 15 mL of 120 mg / L methyl orange (MO) solution, and adsorption was performed at 30°C. 150 μL of the solution supernatant was taken at a preset time point, diluted to 3 mL of solution (diluted 20 times), and the MO (wavelength λ max =464nm) solution absorbance. According to the standard curve, the corresponding concentration is obtained and the adsorption capacity of the adsorbent is calculated. The test results are as follows: Figure 4 shown.
[0044] The adsorption kinetics curve of methyl orange ( Figure 4 ) It can be seen that compared with CPAM / GO and PEI / GO prepared by the same method, CPAM / PEI / GO has a stronger adsorption capacity for MO. The main reason is that CPAM / PEI / GO has more wrinkles and holes, which on the one hand increases the contact area between the adsorbent and MO, and on the other hand provides more active adsorption sites, which is beneficial to the adsorption process. The main difference between the implementation samples CPAM / PEI / GO (1) and CPAM / PEI / GO (2) is that the amount of PEI added in the preparation of graphene oxide-based composite aerogel adsorbent is different, which affects the activity and number of the adsorption sites of the adsorbent, and then affects the adsorption performance of the adsorbent. Figure 4 It can be seen that increasing the PEI content of the composite aerogel is beneficial to improving the adsorption performance of the aerogel.
Claims
1. A method for preparing a graphene oxide-based composite aerogel adsorbent, characterized in that: Add acrylamide to the graphene oxide suspension and mix evenly to obtain a mixed suspension; add ammonium persulfate and N,N-methylene acrylamide to methacryloyloxyethyl trimethyl ammonium chloride and mix thoroughly to obtain a prepolymer solution; add a polyethyleneimine aqueous solution to the prepolymer solution to obtain a pre-reaction solution; add the pre-reaction solution to the mixed suspension, and sequentially add an ammonium persulfate aqueous solution and an N,N-methylene acrylamide aqueous solution dropwise thereto, and sequentially perform stirring, gelling reaction, washing and freeze-drying to obtain; The concentration of the graphene oxide suspension is 1-20 mg / mL; the mass ratio of graphene oxide to acrylamide in the mixed suspension is 1:5-1:50; The mass ratio of the methacryloyloxyethyltrimethylammonium chloride to the graphene oxide is 10-100:1; The volume ratio of the polyethyleneimine aqueous solution to the prepolymer solution is 0.5-3:1; The mass ratio of the polyethyleneimine to graphene oxide is 5-100:
1.
2. The method for preparing a graphene oxide-based composite aerogel adsorbent according to claim 1, characterized in that: The mass ratio of the methacryloyloxyethyltrimethylammonium chloride to ammonium persulfate is 20-400:1; the mass ratio of the methacryloyloxyethyltrimethylammonium chloride to N,N-methylene acrylamide is 10-400:
1.
3. The method for preparing a graphene oxide-based composite aerogel adsorbent according to claim 1, characterized in that: The mass ratio of ammonium persulfate added to the pre-reaction liquid to methacryloyloxyethyltrimethylammonium chloride is 1:500-1:10; the mass ratio of N,N-methyleneacrylamide added to the pre-reaction liquid to methacryloyloxyethyltrimethylammonium chloride is 1:500-1:
5.
4. A method for preparing a graphene oxide-based composite aerogel adsorbent according to any one of claims 1 to 3, characterized in that: The conditions of the gelling reaction are: temperature of 80-120° C. and time of 8-24 h.
5. A graphene oxide-based composite aerogel, characterized in that: Obtained by the preparation method according to any one of claims 1 to 4.
6. The use of a graphene oxide-based composite aerogel according to claim 5, characterized in that: Used to adsorb organic pollutants in sewage.
Citation Information
Patent Citations
Macro preparation method of macroscopic three-dimensional graphene aerogel adsorption material used for indoor air purification
CN103407997A
Preparation method of magnetic polymer dye adsorbent
CN107376870A